2020
DOI: 10.21203/rs.3.rs-42747/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Silico Approach of Potential Phytochemical Inhibitor from Moringa oleifera, Cocos nucifera, Allium cepa, Psidium guajava, and Eucalyptus globulus for the treatment of COVID-19 by Molecular Docking

Abstract: Background Coronavirus disease 2019 (COVID-19) is caused by infection with severe acute respiratory syndrome coronavirus 2. COVID-19 has devastating effects on people in all countries and getting worse. We aim to investigate an in-silico docking analysis of phytochemical compounds from medicinal plants that used to combat inhibition of the COVID-19 pathway. There are several phytochemicals in medicinal plants, however, the mechanism of bioactive compounds remains unclear. These results are obtained from in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
(31 reference statements)
0
10
0
2
Order By: Relevance
“…Similarly, phytochemicals such as Allium cepa L. oleanolic acids, Cocos nucifera L. α-tocotrienols, Psidium guajava L. asiatic acids, and Eucalyptus globulus culinosides exhibit anti-SARS-CoV-2 activity in molecular dynamic docking analysis. Oleanolic acid specifically binds to the Mpro enzyme (Fitriani et al, 2020).…”
Section: Inhibition Of Sars-cov Mpro Plpro 3clpro and Related Proteasesmentioning
confidence: 99%
“…Similarly, phytochemicals such as Allium cepa L. oleanolic acids, Cocos nucifera L. α-tocotrienols, Psidium guajava L. asiatic acids, and Eucalyptus globulus culinosides exhibit anti-SARS-CoV-2 activity in molecular dynamic docking analysis. Oleanolic acid specifically binds to the Mpro enzyme (Fitriani et al, 2020).…”
Section: Inhibition Of Sars-cov Mpro Plpro 3clpro and Related Proteasesmentioning
confidence: 99%
“…Considering the crucial role of inflammation in the neuropathogenesis of COVID-19, phytochemicals with neuronal anti-inflammatory effects could pave the road in combating related neuronal manifestations. Recent reports also have declared the critical role of phytochemicals in health care through their antiviral ( Fitriani et al, 2020 ) and the inhibition of neuroinflammatory-interconnected pathways ( Abbaszadeh et al, 2020 ). Phytochemicals with potential antioxidant and anti-inflammatory effects (e.g., carotenoids and polyphenols) interact with major transcription factors such as Nrf2 and NF-κB ( Iddir et al, 2020 ).…”
Section: Potential Of Phytochemicals Against Covid-19 Neurological Asmentioning
confidence: 99%
“…Recently, a new strain of coronaviruses, namely SARS-CoV-2 has been found, belonging to a distinct class of beta coronaviruses ( Divani et al, 2020 ). SARS-CoV-2 made a deadly disease, termed coronavirus disease 2019 (COVID-19) with devastating manifestation all over the world ( Fitriani et al, 2020 ; Nemoto et al, 2020 ). The large and positive sense RNA genome with a size of 27–32 kb, as well as an envelope with spike (S1 and S2)/conjugated proteins ( Holmes and Lai, 1996 ; Davidson et al, 2020 ) are associated with COVID-19 symptoms over a period of 2–14 days.…”
Section: Introductionmentioning
confidence: 99%
“…The underground stem called the bulb has lot of store of various phytochemicals like various types of polyphenols and flavonoids. Fitriani et al [34] in their study using molecular docking techniques showed the highest binding energy of the pentacyclic triterpenoid oleanolic acid found in the onions with the SARS-CoV 2 Main protease (Mpro) via hydrogen bonding. Though further works need to be done but this study undoubtedly provides evidence for onion based phytochemicals to be a successful candidate for COVID-19 treatment.…”
Section: Allium Cepa Lmentioning
confidence: 99%